2007
DOI: 10.1097/nrl.0b013e31811e9d6d
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Zoster Paresis of Limbs

Abstract: Segmental zoster paresis is still underrecognized by neurologists. Awareness of this disorder is important because it may eliminate unnecessary invasive investigations and lead to appropriate treatment. Further studies on the treatment are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Normally, MRI scanning is not performed in patients with uncomplicated zoster. A PubMed search of patients with zoster paresis (lower motor neuron weakness corresponding to the dermatome where rash was present) revealed that MRI scans are normal [1-4] or that spinal cord lesions are present 1-2 levels adjacent to the area of segmental weakness [5-7]. Thus, to our knowledge, this is the first report of widespread subclinical imaging abnormalities far beyond the site of zoster and focal zoster paresis.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, MRI scanning is not performed in patients with uncomplicated zoster. A PubMed search of patients with zoster paresis (lower motor neuron weakness corresponding to the dermatome where rash was present) revealed that MRI scans are normal [1-4] or that spinal cord lesions are present 1-2 levels adjacent to the area of segmental weakness [5-7]. Thus, to our knowledge, this is the first report of widespread subclinical imaging abnormalities far beyond the site of zoster and focal zoster paresis.…”
Section: Discussionmentioning
confidence: 99%
“…Paresis of the ipsilateral shoulder or arm [473477], occurs in 3–5% of HZ cases, but is underdiagnosed [478, 479]. Some cases are due to brachial plexopathy [480, 481], and others to Brown-Séquard hemiplegia [460, 482].…”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…It is usually presented as a self-limiting vesicular rash, often accompanied by post-herpetic neuralgia [ 3 ]. Though relatively rare, the virus can affect the corresponding myotome and cause motor weakness or paresis after VZV reactivation [ 4 - 6 ]. If the virus affects the lower motor nerve, the symptom may mimic sciatica or paresis caused by the lumbar spine lesion [ 7 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The localization of motor abnormality can be also challenging because the involved myotomes do not always correspond to the dermatomes affected by a zoster skin rash [ 14 ]. The EMG-NCV tests have been generally used to evaluate the extent of herpes zoster-associated neuropathy [ 4 , 12 - 13 , 15 ]. However, the accuracy of those studies may vary depending on the physician’s skill and often difficult to test immediately.…”
Section: Discussionmentioning
confidence: 99%